2020
DOI: 10.1039/d0ra06592g
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of polyaspartic acid derivative PASP-Im and investigation of its scale inhibition performance and mechanism in industrial circulating water

Abstract: A polyaspartic acid derivative (PASP-Im) as a novel scale inhibitor was synthesized by a simple green synthesis route with polysuccinimide and iminodiacetic acid as the starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…Tables and tabulated the obtained experimental results from the DSR for calcite and barite scales, respectively. It was reported that polyaspartic acid afforded good scale and corrosion inhibition performance for cooling water system applications. For the oilfield calcite scaling, SI-1 gave very good inhibition activity with an FIC of 5 ppm after 6 and 5 min for both runs, respectively (Table ).…”
Section: Results and Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Tables and tabulated the obtained experimental results from the DSR for calcite and barite scales, respectively. It was reported that polyaspartic acid afforded good scale and corrosion inhibition performance for cooling water system applications. For the oilfield calcite scaling, SI-1 gave very good inhibition activity with an FIC of 5 ppm after 6 and 5 min for both runs, respectively (Table ).…”
Section: Results and Discussionmentioning
confidence: 97%
“…We have synthesized in-house polyaspartic acid ( SI-1 ) via the alkaline hydrolysis of polysuccinimide (Figure , route A), as reported previously in the literature. To characterize the obtained polyaspartic acid ( SI-1 ), FTIR and NMR spectroscopy techniques were used. FTIR spectra of SI-1 displayed a broad absorption peak at 3300 cm –1 attributed to the N–H bond stretching vibration, the band at 1706 cm –1 revealed the CO of carboxyl, and the absorption band at 1568 revealed the stretching vibration of the CO bond of the amide moiety.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, many chemical scale inhibitors have been applied to the prevention and control of oilfield scale, but the scale inhibition efficiency is low and the cost is high. Commercial scale inhibitors for carbonate and sulfate scaling are usually polymers, such as poly­(acrylic acid), polymaleic anhydride, polyphosphate, etc. Polyphosphonic acid scale inhibitors play a key role in the performance of oilfield scale inhibition, and they are also the most widely used . However, most of the phosphonic acid scale inhibitors currently on the market, such as amino trimethylene phosphonic acid (ATMP) and ethylene diamine tetramethylene phosphonic acid (EDTMPA), have poor compatibility with calcium ions and will cause complex precipitation .…”
Section: Introductionmentioning
confidence: 99%